INTEGRATED READING AND COMPOSITIONOF SELECTED LEARNING MATRIALTO FOR ESP STUDENTS’ COMPREHENSION - Antoni, Rivi (Universitas Pasir Pengaraian, 2013)
This research reports the investigation on the use of using Integrated Readingand Composition (IRC) in teaching TEFL II at class VI/A of English departmentstudents of university of Pasir Pengaraian in academic year 2013/2014. The purposesof this study were to find outto what extent can integrated reading and composition(IRC) improve students’ reading comprehension of selected learning materials of ESPat Class VI/A of English department students of Pasir Pengaraian university? And (2)what factors influence the changes of students’ reading comprehension of the selectedmaterials by using IRC.This research used classroom action research designconsisted of two cycles and the instruments used were test, observation and interview.The data were analyzed quantitatively and qualitatively